Cardiovascular Genetic Risk Testing for Targeting Statin Therapy in the Primary Prevention of Atherosclerotic Cardiovascular Disease: A Cost-Effectiveness Analysis. Issue 4 (April 2018) - Jarmul, Jamie; Pletcher, Mark J.; Hassmiller Lich, Kristen; Wheeler, Stephanie B.; Weinberger, Morris; Avery, Christy L.; Jonas, Daniel E.; Earnshaw, Stephanie; Pignone, Michael
Abstract : Background: It is unclear whether testing for novel risk factors, such as a cardiovascular genetic risk score (cGRS), improves clinical decision making or health outcomes when used for targeting statin initiation in the primary prevention of atherosclerotic cardiovascular disease (ASCVD). Our objective was to estimate the cost-effectiveness of cGRS testing to inform clinical decision making about statin initiation in individuals with low-to-intermediate (2.5%–7.5%) 10-year predicted risk of ASCVD. Methods and Results: We evaluated the cost-effectiveness of testing for a 27-single-nucleotide polymorphism cGRS comparing 4 test/treat strategies: treat all, treat none, test/treat if cGRS is high, and test/treat if cGRS is intermediate or high. We tested a set of clinical scenarios of men and women, aged 45 to 65 years, with 10-year ASCVD risks between 2.5% and 7.5%. Our primary outcome measure was cost per quality-adjusted life-year gained. Under base case assumptions for statin disutility and cost, the preferred strategy is to treat all patients with ASCVD risk >2.5% without cGRS testing. For certain clinical scenarios, such as a 57-year-old man with a 10-year ASCVD risk of 7.5%, cGRS testing can be cost-effective under a limited set of assumptions; for example, when statins cost 15 per month and statin disutility is 0.013 (ie, willing to trade 3 months of life in perfect health to avoid 20 years of statin therapy), the preferred strategy (using a willingness-to-pay threshold of 50 000 per quality-adjusted life-year gained) is to test and treat if cGRS is intermediate or high. Overall, the results were not sensitive to assumptions about statin efficacy and harms. Conclusions: Testing for a 27-single-nucleotide polymorphism cGRS is generally not a cost-effective approach for targeting statin therapy in the primary prevention of ASCVD for low- to intermediate-risk patients. Abstract : Supplemental Digital Content is available in the text.